2002
DOI: 10.1097/00000478-200212000-00006
|View full text |Cite
|
Sign up to set email alerts
|

P504S Immunohistochemical Detection in 405 Prostatic Specimens Including 376 18-Gauge Needle Biopsies

Abstract: P504S is a recently described, prostate cancer-specific gene that encodes a protein involved in the beta-oxidation of branched chain fatty acids. A recent study has shown that immunohistochemical detection of P504S gene product is a sensitive and specific marker of prostatic carcinoma in formalin-fixed, paraffin-embedded tissues. We performed a detailed analysis of P504S protein expression in a large series of prostate and bladder specimens with special emphasis on staining in specific morphologic patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
149
4
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(171 citation statements)
references
References 8 publications
13
149
4
5
Order By: Relevance
“…This confirms the results of Beach et al, 5 who reported expression in 32% of the cases. 5 In our experience, we observed a weaker intensity of expression of p504s in high-grade prostatic intraepithelial neoplasias compared to prostatic carcinomas.…”
Section: Diagnostic Utility Of a P63/amacr (P504s) V Molinié Et Alsupporting
confidence: 93%
See 4 more Smart Citations
“…This confirms the results of Beach et al, 5 who reported expression in 32% of the cases. 5 In our experience, we observed a weaker intensity of expression of p504s in high-grade prostatic intraepithelial neoplasias compared to prostatic carcinomas.…”
Section: Diagnostic Utility Of a P63/amacr (P504s) V Molinié Et Alsupporting
confidence: 93%
“…The application, in our series, of coexistent antibody again basal cells (p63) demonstrated that these glands had fewer basalstained than nonpositive p504s normal glands and led us to believe that this could be interpreted as low-grade prostatic intraepithelial neoplasia ( Figure 8). This result is not concordant with the 21% reported by Beach et al 5 Like those authors, we also observed that this expression is generally focal and is weaker than the positivity of the tumoral prostatic glands. 5 The increased AMACR expression by some normal prostatic glands could reflect upregulation of metabolic pathways of prostate glands during the carcinogenic process.…”
Section: Diagnostic Utility Of a P63/amacr (P504s) V Molinié Et Alcontrasting
confidence: 90%
See 3 more Smart Citations